Sexual Fantasies and Stereotypical Gender Roles: The Influence of Sexual Orientation, Gender and Social Pressure in a Sample of Italian Young-Adults - Tortora, Carla; D’Urso, Giulio; Nimbi, Filippo M.; Pace, Ugo; Marchetti, Daniela; Fontanesi, Lilybeth (Frontiers in Psychology, 2020)
Differences in gender and sexual orientation are suggested to be linked to differences in the way individuals think and behave. The aim of the current study is to evaluate the effect of gender and sexual orientation on sexual fantasies and gender roles, in heterosexual and homosexual people. The sample was composed of 547 participants, 246 men (Mage=28.85; S.D.=9,27) and 301 women (Mage=25,97; S.D.=7,141). 61,8% of men and 79,4% of women were heterosexual; 38,2% of men and 20,6% of women were homosexual. Participants completed an online battery of questionnaires to assess the sexual orientation of the participants, their sexual fantasies, and gender roles on three different dimensions. It was hypothesized that the heterosexual group would report more normative sexual fantasies (H1), and that women in general would report androgynous characteristics, which would be linked to low feminine ideal roles and high social pressure to conform to social feminine expectations (H2). The results showed how lesbian women scored slightly higher than heterosexual women on transgressive sexual fantasies and lower on emotional-romantic ones. Moreover, heterosexual women, but not lesbian women, showed a pattern of high social pressure to conform to feminine expectations together with lower scores in the IRQ. We found the same results on gay men but not for heterosexual men. Finally, the overall results suggest that sexual fantasies and gender roles are relatively independent concepts, influenced by different mechanisms.